2022
DOI: 10.1002/jcsm.13129
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of physical and mental functioning over 25 years before onset of frailty: results from the Whitehall II cohort study

Abstract: Background Research on frailty, a major contributor to heterogeneity in health, is undertaken on older adults although the processes leading to frailty are likely to begin earlier in the life course. Using repeat data spanning 25 years, we examined changes in physical and mental functioning before the onset of frailty, defined using Fried's frailty phenotype (FFP). Methods Functioning was measured using the Short-Form 36 General Health Survey (SF-36) on nine occasions from 1991 (age range 40-63 years) to 2015 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…After screening 5681 articles by title and abstract, 84 articles were retrieved for eligibility analyses through a full-text reading. Of these, 33 articles were finally selected [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. Each section may be divided by subheadings.…”
Section: Resultsmentioning
confidence: 99%
“…After screening 5681 articles by title and abstract, 84 articles were retrieved for eligibility analyses through a full-text reading. Of these, 33 articles were finally selected [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. Each section may be divided by subheadings.…”
Section: Resultsmentioning
confidence: 99%
“…Both individuals classified as frail and pre-frail exhibited significantly diminished scores in mental and physical quality of life compared to non-frail individuals ( 33 ). A 25-year study utilizing replicated data revealed that individuals experiencing frailty exhibited significantly lower scores in the Short-Form 36 General Health Survey (SF-36) in comparison to non-frailty individuals ( 34 ). For instance, a prior study conducted in western China, involving 4,103 community residents aged 60 years and older, revealed that individuals grappling with co-morbidities of depression and anxiety exhibited elevated odds of pre-frailty (OR=1.86, 95% CI=1.41-2.45) and frailty (OR=7.03, 95% CI=4.48-11.05) in contrast to individuals without depressive and anxiety symptoms ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…5 This patient-reported outcome has strong links to more traditional health outcomes, such as mortality in general population 6 or survival in cancer patients, 7 and often precedes declines in objective health by years, especially in elderly patients. 8 While HRQoL in subjects with current long-term environmental exposures to chemicals or pollution has been the focus of a few studies, 9,10 none investigated the aftermath of these exposures. Former asbestos-exposed workers live with the knowledge that they have been exposed to a dangerous substance and that they might someday fall ill, a situation that Leibovits 11 likened to that of healthy genetic cancer carriers.…”
Section: Introductionmentioning
confidence: 99%
“…Health‐related quality of life (HRQoL) can be defined as “the health aspects of quality of life, generally considered to reflect the impact of disease and treatment on disability and daily functioning” and it also reflects “the impact of perceived health on an individual's ability to live a fulfilling life.” 5 This patient‐reported outcome has strong links to more traditional health outcomes, such as mortality in general population 6 or survival in cancer patients, 7 and often precedes declines in objective health by years, especially in elderly patients 8 …”
Section: Introductionmentioning
confidence: 99%